Antecedents and outcomes of brand prominence on willingness to buy luxury brands - Cheah, Isaac; Phau, Ian; Chong, C.; Shimul, A. (Emerald, 2015)
Purpose: The purpose of this paper is to investigate the influence of brand prominence on willingness to buy luxury brands. It also aims to investigate the direct and moderating roles of luxury brand values, social influence and vanity on willingness to buy luxury brands. Design/methodology/approach: A convenience sampling method was employed. Survey questionnaires were distributed by mall intercept to quasi-random samples in downtown Perth, Western Australia for completion and return. The return yielded 779 usable questionnaires, the data from which were analysed using SPSS 22. Findings: The findings support the influence of brand prominence on purchase intention for luxury brands. It has also been found that social influence has a significant influence on physical vanity and willingness to buy luxury brands. However, some relationships with and isolations from the earlier studies have been identified. Practical implications: This study provides some meaningful insights for marketing managers regarding brands prominence that they can use in better understanding the consumers’ intention to buy luxury products. A luxury goods manufacturer may want to be cautious to not over popularize its trademark for short-term gains. There must be a delicate balance between the uses of prominent and subtle signals in luxury branding in order to maintain value as a prestigious label. Originality/value: Previous studies have mainly focused on the antecedents of willingness to buy luxury brands, whereas this paper incorporates the construct of brand prominence, adding new insights into the construct.